Crop damage caused by powdery mildew on hop and its relationship to late season management. (26th August 2013) - Gent, D. H.; Grove, G. G.; Nelson, M. E.; Wolfenbarger, S. N.; Woods, J. L.
<x xml:space="preserve">Abstract</x> Powdery mildew of hop (Podosphaera macularis) may cause economic loss due to reductions in cone yield and quality. Quantitative estimates of crop damage from powdery mildew remain poorly characterized, especially the effect of late season disease management on crop yield and quality. Field studies in Washington State evaluated cone yield, bittering acid content and quality factors when fungicide applications were ceased at different stages of cone development. The incidence of cones with powdery mildew was linearly correlated with yield of cones, bittering acids and accelerated cone maturation. In cultivar Galena, the cumulative effect of every 1% increase in cones powdery mildew incidence was to reduce alpha‐acid yield by 0·33%, which was due to direct effects on cone yield but also indirect effects mediated by dry matter. In the more susceptible cultivar Zeus, alpha‐acid yield was increased 20% by controlling powdery mildew through the transition of bloom to early cone development compared to ceasing fungicide applications at bloom: additional applications provided only modest improvements in alpha‐acid yield. In both cultivars, the impact of powdery mildew on aroma characteristics and bittering acid content were less substantial than cone yield. The damage caused by powdery mildew to cone colour and alpha‐acid yield, as well as the effectiveness of fungicide applications made to manage the disease, appears inseparably linked to dry matter content of cones at harvest. Realising achievable yield potential in these cultivars requires control of the disease through early stages of cone development and harvest before maturity exceeds c. 25% dry matter.